Diatom assemblages in surface sediments of Lake Imandra (Russia, Murmansk region) - Vokueva, Sofiya; Denisov, Dmitrii (Polish Polar Research, 2021)
In this article we investigate diatom assemblages in surface sediments of the subarctic Lake Imandra. We examine taxonomic composition and ecological structure and describe spatial variations of diatoms over the lake area. The diatom flora described here are characterized by abundance of planktonic centric species. The habitats of diatoms in the different stretches of Lake Imandra reflect local environmental conditions and are determined by the type and intensity of the anthropogenic impact. Stephanodiscus minutulus, S. alpinus, Aulacoseira islandica are the most abundant species in the area of the lake affected by industrial effluents and eutrophication, while Pantocsekiella comensis is most typical in the background sites of the lake. Diatoms taxonomic diversity is high in shallow bays where aquatic vegetation is common. Abundance of diatoms in areas affected by anthropogenic eutrophication reflects the high intensity of plankton primary production. Differences in the ecological structure of the diatom assemblages in different parts of Lake Imandra are caused by significant hydrochemical heterogeneity of the water quality.